The Magic of the Hotbeds of Research for School Students (2009)
For Santiago Ospina Patiño, participant of the hotbed of research in Physics for school-age children: “It was a surprise for me when they invited me to be part of the hotbeds, which are the second stage of Children's University, only in these you choose a specific field, such as example ecology, culture, economy, among others”.